1992
DOI: 10.2307/1130904
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Separation Anxiety: Its Developmental Course and Relation to Maternal Mental Health

Abstract: Maternal separation anxiety is a construct that describes a mother's experience of worry, sadness, or guilt during short-term separations from her child. This investigation examined potential differences in psychological correlates between mothers with high and low levels of anxiety when their children were 8 months, 3 1/2 years, and 6 years of age. High levels of maternal separation anxiety had different psychological correlates contingent upon the age of the child. Depressive symptomatology and separation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 11 publications
3
47
0
1
Order By: Relevance
“…The abundant research on mothers' anxiety regarding separation from their children supports the belief that maternal anxiety is an important psychological construct and is meaningfully related to both maternal behaviors towards the child and other aspects of maternal personality (e.g., DeMeis, Hock, & McBride, 1986;Hock, Hart, Kang, & Lutz, 2004;Hock, McBride, & Gnezda, 1989;Hock & Schirtzinger, 1992;Lutz & Hock, 1995;McBride & Belsky, 1988). Yet, the familial antecedents of maternal anxiety have not been fully explicated, nor has their impact on children's separation anxiety and their adjustment to kindergarten.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…The abundant research on mothers' anxiety regarding separation from their children supports the belief that maternal anxiety is an important psychological construct and is meaningfully related to both maternal behaviors towards the child and other aspects of maternal personality (e.g., DeMeis, Hock, & McBride, 1986;Hock, Hart, Kang, & Lutz, 2004;Hock, McBride, & Gnezda, 1989;Hock & Schirtzinger, 1992;Lutz & Hock, 1995;McBride & Belsky, 1988). Yet, the familial antecedents of maternal anxiety have not been fully explicated, nor has their impact on children's separation anxiety and their adjustment to kindergarten.…”
Section: Introductionmentioning
confidence: 91%
“…It was found that employed mothers are less anxious about separation than are mothers who are not employed (Stifler et al, 1993). It is argued that mothers who are less traditional in their sex-role behavior have lower levels of separation anxiety than mothers who maintain traditional sex-role behavior (Hock & Schirtzinger, 1992).…”
Section: Eastern Vs Western Culturesmentioning
confidence: 99%
See 2 more Smart Citations
“…As gender identity is more cognitive process than biological phenomenon, measuring this issue needs an accurate and reliable measurement. The Male-Female Relations Questionnaire (MFRQ) (Spence, Helmreich, & Sawin, 1980) had been used in many social science (for example, Hock & Schirtzinger, 2008;McCabe, 2011;Shafiro, Himelein, & Best, 2003) and ethics studies (for example, McCabe et al, 2006). MFRQ Social Interactions sub-scale consists of 16 questions with five-Likert scale as 1 being strongly disagree to 5 being strongly agree.…”
Section: Gender Identity Scalementioning
confidence: 99%